DEVELOPMENT OF OPTICAL SYSTEMS OF 16-LENS ORTHOSCOPIC TELEPHOTO LENSES - SOKURENKO, Vyacheslav; KHUTOROVYI, Ivan; SOKURENKO, Oleg (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In this work, the possibilities of creating multi-lens optical systems of telephoto lenses with a fixed focal length and high image quality with the help of a computer have been experimentally investigated. The effectiveness of the automated procedure for creating new optical systems of orthoscopic telephoto lenses was repeatedly examined. The design procedure utilizes a modified version of the modern stochastic global optimization algorithm. In particular, we carried out the aberration synthesis of several optical systems of 16-lens orthoscopic telephoto lenses having the effective focal length of 300 mm and a F-number equal to 2.8, and designed to work in the visible spectral range with 35-mm full-frame image matrix detectors. Multiple computer simulations of the design process have shown that the global optimization procedure with a total number of variables of around 90 requires significant computing power. Specifically, when running on the Intel Core i9-9900K processor in multi-threaded mode and optimizing the values of the modulation transfer functions, the design procedure can exceed 50 hours. The maximum value of the relative distortion of synthesized variants of telephoto lenses does not exceed 0.017%. In all considered cases, the values of polychromatic modulation transfer functions for a spatial frequency of 30 lines/mm are not smaller than 0.5 over the entire image field. The design results obtained for the specified telephoto lenses confirm the effectiveness of the proposed approach and the practical possibility of achieving high-quality correction of aberrations in the above-mentioned multi-lens telephoto systems even without the use of fluorite (calcium fluoride).